Effect of Solution Concentration on the Adsorption Capacity of Ionic Imprinted Polymer (IIP) for Fe(III) Separation - Aryansyah Tri Wibowo; Maria Monica Sianita Basukiwardojo (Jurnal Pijar MIPA, 2026)
Iron (Fe) contamination in Indonesian waters frequently exceeds the drinking water quality standard (0.3 mg/L) and poses risks to human health and aquatic ecosystems, highlighting the need for a selective and effective removal method. This study aimed to analyze the effect of solution concentration on the adsorption capacity of an EDTA-based Ion Imprinted Polymer (IIP) for Fe(III) ions. The research employed an experimental design through the synthesis of IIP using the precipitation polymerization method, with methacrylic acid (MAA) as the functional monomer, ethylene glycol dimethacrylate (EGDMA) as the crosslinker, and benzoyl peroxide (BPO) as the initiator. Data were collected through characterization using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy with Energy Dispersive X-ray (SEM-EDX), while Fe(III) concentrations were measured using Atomic Absorption Spectrophotometry (AAS). Fe(NO₃)₃ solutions at concentrations ranging from 5 to 35 ppm were tested at neutral pH. Data analysis was conducted by calculating the adsorption capacity as the difference between the initial and final concentrations. The results showed that increasing the initial concentration increased adsorption capacity until equilibrium was reached, with a maximum of 19.06 mg/g. FTIR analysis confirmed the presence of characteristic functional groups and the removal of Fe–O bonds after extraction, while SEM analysis revealed the formation of specific cavities in the IIP structure. In conclusion, the synthesized IIP demonstrates good selectivity and effectiveness for Fe(III) adsorption from aqueous solutions, indicating its potential application as a selective adsorbent for heavy metal-contaminated water treatment.